STRATEGI PENGEMBANGAN PASAR SENGGOL KLUNGKUNG SEBAGAI DESTINASI WISATA KULINER DI BALI - Saskara, I Ketut; Sutrisnawati, Ni Ketut (Akses: Jurnal Penelitian dan Pengabdian Kepada Masyarakat Universitas Ngurah Rai, 2023)
Klungkung is one of the districts in Bali that has various tourism potentials, one of which is culinary potential. One of the culinary destinations for the local community is Pasar Senggol. Pasar Senggol Klungkung is a traditional market that is open from the afternoon until the evening. In Pasar Senggol Klungkung, various types of traditional dishes are sold, such as Serombotan which is a culinary icon of Klungkung district, porridge, traditional snacks and other culinary delights. Pasar Senggol Klungkung has various potentials that can be developed as one of the culinary destinations in Bali. This study aims to find out how the strategy for developing Pasar Senggol Klungkung as a culinary tourism destination in Bali. This study uses a qualitative descriptive analysis technique. Primary data was obtained through direct observation to the research location and interviews with traders at the research location, while secondary data was obtained by conducting a literature study using references to several journals that matched the same topic. The data collected in the form of potential, opportunities, weaknesses and threats were analyzed using the SWOT Matrix method. The results of the study reveal that Pasar Senggol Klungkung has great potential to be developed as a culinary destination. Pasar Senggol is located in the heart of Klungkung city, in the area of the Puputan Klungkung monument and the Kertagosa tourist attraction. This market also offers Klungkung’s traditional food such as Serombotan and other traditional foods that have its own taste.